Gastos de abastecimiento e inversión y demanda universitaria en las facultades de la UNAP durante el periodo 2015 - 2019 - Pizarro Valles, Hernán (2022)
Higher education in Peru, especially in public universities, undertakes a new challenge, within the framework of Law N ° 30220 - Which is the so-called "New University Law" aims to undertake a new quality prospect with a main focus on scientific research through continuous improvement of educational quality with the production of knowledge and development of technologies; However, public university education faces a budgetary restriction in terms of investment and supply expenses. This study seeks to determine the relationship between investment and supply spending and university demand at the National University of the Peruvian Amazon, as well as to determine the relationship of this investment spending with other fundamental determinants of university demand, such as the number of of graduates, university welfare and the number of teachers, this is done through a methodology of non-experimental nature, quantitative and correlational design, specifically a multiple linear regression model is used, in a sample of 21,552 applicants. In this study, we find that an increase of one unit in university demand at UNAP increases investment and supply spending by approximately 237 soles, in the same way we demonstrate the requirement of a positive and significant relationship between supply spending and supply. university, the number of graduates, the number of teachers and university welfare, concluding that in order to increase the number of quality professionals that are integrated into society and the university demand by the population, it is necessary to increase investment in the university, in order to provide better quality of teaching and well-being to future professionals.